Ovarian serous tumor with mural nodule of sarcomatoid carcinoma and reactive changes. - Basheska, Neli; Veljanovska, Slavica; Zografski, George (Springer, 2009)
Background Serous ovarian tumors with mural nodules are very infrequent, with only a dozen of cases described, including four cases of sarcomatoid carcinoma. We report a first case of a mural nodule with features of both sarcomatoid carcinoma and prominent sarcoma-like reactive changes associated with ovarian serous cystic tumor. Methods A 52-year-old woman underwent left salpingooophorectomy and partial omentectomy because of a cyst. Forty-five months previously a total abdominal hysterectomy with right salpingo-oophorectomy and left ovarian resection had been performed. Postoperatively the patient received full-dose chemotherapy and is clinically free of disease at 76 months’ follow-up. Results Within the wall of the largest locule of the left ovarian multilocular cyst, 12.5 cm in diameter that had ruptured at operation, there was a 4x4x1.5 cm nodule. The smaller locules were lined with benign serous epithelium, while the largest locule had morphology of a serous borderline tumor with small foci of superficial invasion. The mural nodule was composed of carcinomatous nests intermingled with pleomorphic mononuclear cells, multinucleated giant cells, histiocytes and other inflammatory cells. The luminal epithelium and underlying pleomorphic cells were diffusely positive for cytokeratin and epithelial membrane antigen, and focally positive for vimentin. Benign spindle cells and multinucleated giant cells were vimentin positive. The ovarian capsule was not invaded. Conclusion(s) This study confirms the usefulness of immunohistochemistry in distinguishing variant forms of mural nodules in cystic ovarian tumors. It further suggests that malignant nodules in serous tumors do not necessarily carry a poor prognosis.
Keywords: ovary; serous tumor; mural nodule; sarcomatoid carcinoma; histopathology; immunohistochemistry; prognosis